(untitled) (Research, Society and Development, 2020)
The objective of the present work was to characterize and microbiologically evaluate different formulations of jams and paste candies of purple pitanga with reduced sucrose contents. The formulations made for jams were “jam A” with a 100% proportion and “jam B” with a 50% proportion, all with the addition of pectin (1.5 g) and citric acid (0.45 g). For the paste candies the concentrations were “candy A” with 60% and “candy B” with 40%, all added with citric acid (0.6 g) and water (36 mL). The elaboration process followed all the quality control standards and, in sequence, the physicochemical (humidity; ash content; soluble solids; pH; titratable acidity; sugars; color parameters; anthocyanins; flavonoids) and microbiological (total and thermotolerant coliforms; molds and yeast; coagulase positive Staphylococcus and Salmonella sp.) characterizations were performed. The results of the analyses have been compare only between formulations of the same type of product. All physicochemical data were within the standard parameters for candies and jams. As for the color aspect, the samples showed a characteristic intense red, differing only in the chromaticity and luminosity parameters in sweets and jellies respectively. The pitanga by-products presented varied concentrations of bioactive compounds, with emphasis on greater amounts of anthocyanin. For all microbiological aspects evaluated, the results were in accordance with the standards established by the legislation. Thus, the possibility of the development of purple pitanga jams and candies has been showned, with a reduction in sucrose content, but with interesting nutritional, microbiological and visual characteristics.